The Arthrobacter Species FB24 Arth_1007 (DnaB) Intein Is a Pseudogene - Tori, Kazuo (Public Library of Science, 2011)
An Arthrobacter species FB24 gene (locus tag Arth_1007) was previously annotated as a putative intein-containing DnaB helicase of phage origin (Arsp-FB24 DnaB intein). However, it is not a helicase gene because the sequence similarity is limited to inteins. In fact, the flanking exteins total only 66 amino acids. Therefore, the intein should be referred to as the Arsp-FB24 Arth_1007 intein. The Arsp-FB24 Arth_1007 intein failed to splice in its native precursor and in a model precursor. We previously noted that the Arsp-FB24 Arth_1007 intein is the only putative Class 3 intein that is missing the catalytically essential Cys at position 4 of intein Motif F, which is one of the three defining signature residues of this class. Additionally, a catalytically essential His in position 10 of intein Motif B is also absent; this His is the most conserved residue amongst all inteins. Splicing activity was not rescued when these two catalytically important positions were ‘reverted’ back to their consensus residues. This study restores the unity of the Class 3 intein signature sequence in active inteins by demonstrating that the Arsp-FB24 Arth_1007 intein is an inactive pseudogene.